The Muting of the Other: The Technological Reconfiguration of Our Auditory Experience of Others - Gutierrez Ivan (De Gruyter, 2021)
Increasingly privatized auditory spaces resulting from the mutual engendering of auditory cultural practices and sound technologies that separated the sense of hearing and segmented acoustic spaces have had a muting effect on our experience of Others that has intensified since the advent of mobile listening devices. In Section 1 of the article, I outline features of the social realm of the nineteenth to twentieth centuries that made modern sound technologies possible and then features of the technological realm that have shaped today’s social realm – all with an eye toward our experience of other people. Then, in Section 2, I reach for a few phenomenological tools from the work of Jean-Paul Sartre, Emmanuel Levinas, and Don Ihde to draw out the phenomenological vectors that have taken shape within the enmeshed sociotechnological context described in Section 1. Specifically, I show how technologically mediated auditory experience has been individualized and how the use of sound technologies on the go – whether wearing earphones or in a car – has had a muting effect on our experience of others.